Playing Out: A Movement for Movement? - Pike, Elizabeth C. J.; Page, Angie; Vinas, Veronica (Frontiers in Sociology, 2018)
In 2009, the ‘Playing Out’ project was set up in Bristol in the United Kingdom by a parent-led community group who were seeking to address concerns about the lack of freedom for young people to play outside. Playing Out has, as its primary purpose, supporting children to ‘play out’ where they live through providing the space within which children might engage in informal play and physical activity, while also improving relations between neighbours and developing a sense of community. This paper examines the potential of Playing Out for fostering community cohesion by undertaking interviews with participants, officials and policy-makers, alongside some observation of Playing Out events, between 2013-2016. In particular, we evaluate the significance of social capital for the development, and success, of a community-led initiative to influence policy outcomes and increase physical activity levels in the local population, giving consideration to the ways in which social movement concepts build on, and strengthen, social capital. In many societies, such activities take place within a context of neoliberalism, where social order is viewed as being dependent on individual responsibility: governments are deregulated, social programs are cut and/or privatized, and social problems have to be solved by individual, private solutions. Our findings draw on the work of Putnam (1993, 1996, 2000) to demonstrate that social capital is both cause and effect in the success of initiatives such as Playing Out, and that when social capital is combined with elements of a social movement, there can be more fundamental and sustained outcomes.